Pertumbuhan semai sengon dan mangium pada tanah padat - Juang Rata Matangaran; Cahyo Wibowo; Ujang Suwarna (Jurnal Ilmu Pertanian Indonesia, 2010)
The research was conducted to examine the seedling of mangium (Acacia mangium and sengon (Paraserianthes falcataria) on compacted soil. Soil was compacted with a proctor test at the different level of bulk density (0.9;1.0; 1.1; 1.2; 1.3 g/cm3 ) with 10 replications. The compacted soil was put into the plastic pot. After 6 month growth in pot the seedling growth response was measured.The result showed that the root penetration and seedling height linearly decrease with the increase of bulk density. The root of seedling of mangium (Acacia mangium and sengon (Paraserianthes fa/cataria) could not penetrate deeply at the hardest soil (1.3 g/cm3 ). Roots needs space to grow. The space was occupied by soil particles and soil pores. Root may influence chemical and physical properties of soil. In related to the compacted soil the root penetration is the important variable which is affected by the soil hardness. Under the condition of decrease penetration, seedling can not grew well in lack of nutrient to be absorbed by the root. On the other hand the bulk density 1.3 g/cm3 showed difference for seedling height response. However, the growth response was significantly reduced at the level of 1.3 g/cm3. The bulk density 1,3 g/cm3 was the critical limit of soil hardness for the seedling of Mangium and Sengon growth.